Retenção de óleo de café verde em complexos coacervados de proteínas concentradas do soro de leite ou soja e goma arábica - Maggioli , Mirtza Fúlvia (2014)
This work shows the green coffee oil coacervation processes, as core material, in two different systems: whey protein / gum arabic and soy protein / gum arabic, as biopolymer wall. The biopolymers concentration were fixed in 4% (weight / weight) of the emulsion, and the proportion between then was respectively 2:1 and 1,4:1. Different emulsions were made, each one with a different green coffee oil concentration (0%, 10%, 17.5% and 25%) compared with wall materials. From these emulsions with adjusted pH, the system presented phase separation (coacervation). The following system characteristics were studied: maximum interation pHs, emulsions rheological behavior, emulsions sizes, physico-chemical characterization of the phases (coacervate and supernadant), process mass balance, coacervate rheology, microparticles morphology after lyophilization, the powder density, the powder stability and the microencapsulation process efficiency. The results confirmed that there is an optimum range of particle formation, depending on pH. The emulsions presented typical Newtonian fluid behavior and the viscosity increased with incresing the oil concentration. That behavior does not depend on wall materials. It was also observed that wet coacervates were better fitted to Power Law, presenting pseudoplastic behavior. Concentrate soy protein / gum arabic showed thixotropy. The emulsion gout showed an surface average diameter between 2,24 µm e 14,42µm. The microparticles exhibited slightly spherical, rough surface and pores, probably influenced by drying process. The process efficiency showed no dependence on the oil concentration at studied systems. The adsorption isotherms (at 30°C) of the obtained powders were best fitted to the GAB model and the e moisture content of monolayer (xm) for this model were between 2.5% to 5.1% for CPSL and GA microparticles and between 5.1% and 6.1% for IPS and GA